Improving recruitment to primary care trials some lessons from the use of modern marketing techniques - Colwell, B.; Mathers, N.; Ng, C.J.; Bradley, A. (2012)
Successful recruitment to primary care studies is critical if high quality research is to be undertaken and if the research findings are to be representative of the population being researched.1 However, a recent survey of UK primary care trials found that problems with recruitment was the norm; for example, over half of the trials reported in one study ran past their recruitment timetable or had to seek additional funding to complete their data collection.2 Non-completion of studies is costly both in economic terms as well as in participants time. It is discouraging to the participation of primary care professionals in research if it is perceived that completion of a trial is both difficult and a potential waste of their resources. Non-completion can also increase the reluctance of funders to support primary care research.3â5 In an effort to facilitate primary care research, the National Institute for Health Research (NIHR) Primary Care Research Network (PCRN) was set up in 2006. One of its key aims is to provide local researchers with the means to achieve better recruitment into primary care studies.6 Since the PCRNâs inception, it has become clear that there is not a âone size fits allâ recruitment strategy. There are marked differences between the approaches adopted by academia and industry to trial recruitment: in industry, practices may be treated as a âresearch substrateâ rather than as âactive partnersâ (the NIHR approach) and are generally offered financial incentives for each individual patient recruited.7 Other differences include a greater emphasis on marketing and communication strategies by industry and recognition of the need to create a âstrong identityâ for the study, reinforced by project material that has a âstrong visual impactâ.6 As the demand on general practice time grows, there is the real risk that invitations to take part in research will be buried among the myriad communications received by general practices. In industry, marketing techniques, such as viral marketing, have been developed to maximise âproduct identificationâ and to spread the message as widely as possible in the most memorable way to attract public attention, which is ultimately reflected in increased sales.8 Viral marketing depends on a high âpass-alongâ rate to deliver a message transmitted in an âexponentially growing wayâ.9,10 Many criteria must be met for viral marketing to be successful but for the purpose of this study we aimed to use three basic criteria for the recruitment of general practices to a research project; in other words, âgiving the right message to the right messengers in the right environmentâ.9 This paper describes the recruitment strategies employed by a research team to recruit practices and patients to a randomised controlled trial of a patient decision aid (PANDAs), that supports shared decision making by clinicians and people with type 2 diabetes mellitus. It describes how the research team approached and maximised the recruitment of practices using a combination of modified marketing techniques and traditional recruitment methods (Box 1 and 2).